2017
DOI: 10.1155/2017/5760254
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter lwoffii Peritonitis in a Patient on Automated Peritoneal Dialysis: A Case Report and Review of the Literature

Abstract: Acinetobacter lwoffii, a nonfermentative gram-negative aerobic bacillus, which presents in the normal flora of the oropharynx and skin, has recently been reported as a cause of human infection. Herein, the authors present a case report of peritonitis related to automated peritoneal dialysis caused by A. lwoffii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…Thus far, no C. elegans in vivo-studies concerning these two bacteria have been reported in the literature, but their potential pathogeny for humans is well known. Bacteremia and infections caused by A. iwoffii and M. luteus are mostly registered as healthcare-associated infections [69][70][71][72]. In comparison with other microorganisms, the two isolates showed certain pathogenic behaviors because they caused all the typical symptoms and phenotypes of a C. elegans infection, as reported by Ewbank and Pujol [73].…”
Section: In Vivo Assaymentioning
confidence: 80%
“…Thus far, no C. elegans in vivo-studies concerning these two bacteria have been reported in the literature, but their potential pathogeny for humans is well known. Bacteremia and infections caused by A. iwoffii and M. luteus are mostly registered as healthcare-associated infections [69][70][71][72]. In comparison with other microorganisms, the two isolates showed certain pathogenic behaviors because they caused all the typical symptoms and phenotypes of a C. elegans infection, as reported by Ewbank and Pujol [73].…”
Section: In Vivo Assaymentioning
confidence: 80%
“…36 Acinetobacter iwoffii can cause HAIs in patients with chronic illnesses andincreases the length of hospitalisation and mortality. 37 Leclercia adecarboxylata commonly affects immunocompromised individuals, and whilst being susceptible to antibiotics, resistant strains have now been identified. 38 Thirty-nine microorganisms were cultured in total.…”
Section: Discussionmentioning
confidence: 99%
“…For the resistant isolates, therapeutic options are colistin, polymyxin and tigecycline. 10 In this case, empirical antibiotic treatment had been changed to targeted therapy with cefoperazone-sulbactam 750 mg thrice daily intravenously based on antibiotic sensitivity pattern. According to our best knowledge from different literatures, there is no clue for the optimal antibiotic treatment period for A. johnsonii peritonitis.…”
Section: Discussionmentioning
confidence: 99%